The Association of Endothelin‐1 Signaling with Bone Alkaline Phosphatase Expression and Protumorigenic Activities in Canine Osteosarcoma. (1st October 2015) - Neumann, Z.L.; Pondenis, H.C.; Masyr, A.; Byrum, M.L.; Wycislo, K.L.; Fan, T.M.
Abstract : Background: Canine osteosarcoma (OS) is an aggressive sarcoma characterized by pathologic skeletal resorption and pulmonary metastases. A number of negative prognostic factors, including bone alkaline phosphatase, have been identified in dogs with OS, but the underlying biologic factors responsible for such observations have not been thoroughly investigated. Endothelin‐1‐mediated signaling is active during bone repair, and is responsible for osteoblast migration, survival, proliferation, and bone alkaline phosphatase expression. Hypothesis: The endothelin‐1 signaling axis is active in canine OS cells, and this pathway is utilized by malignant osteoblasts for promoting cellular migration, survival, proliferation, and bone alkaline phosphatase activities. Animals: 45 dogs with appendicular OS. Methods: The expressions of endothelin‐1 and endothelin A receptor were studied in OS cell lines and in samples from spontaneously occurring tumors. Activities mediated by endothelin‐1 signaling were investigated by characterizing responses in 3 OS cell lines. In 45 dogs with OS, bone alkaline phosphatase concentrations were correlated with primary tumor osteoproductivity. Results: Canine OS cells express endothelin‐1 and endothelin A receptor, and this signaling axis mediates OS migration, survival, proliferation, and bone alkaline phosphatase activities. In OS‐bearing dogs, circulating bone alkaline phosphatase activities were positively correlated with primary tumor relative bone mineral densities. Conclusions and Clinical Importance: Canine OS cells express endothelin‐1 and functional endothelin A receptors, with the potential for a protumorigenic signaling loop. Increases in bone alkaline phosphatase activity are associated with osteoblastic OS lesions, and might be an epiphenomenon of active endothelin‐1 signaling or excessive osteoproduction within the localized bone microenvironment.